Giair pt a) (x – 1)(x^2 + x + 1) – 2x = x(x – 1)(x + 1) b) x^2 – 3x – 4 = 0

Question

Giair pt
a) (x – 1)(x^2 + x + 1) – 2x = x(x – 1)(x + 1)
b) x^2 – 3x – 4 = 0

in progress 0
Daisy 3 tháng 2021-09-15T22:45:15+00:00 2 Answers 9 views 0

Answers ( )

    0
    2021-09-15T22:46:27+00:00

    `a)(x–1)(x^2+x+1)–2x=x(x – 1)(x + 1)`

    `⇔x^3–1–2x=x(x^2–1)`

    `⇔x^2–1–2x=x^3–x`

    `⇔-2x+x=1⇔-x=1⇔x=-1`

    Tập nghiệm của phương trình: `S={-1}`

    `b)x^2– 3x–4=0`

    `⇔2x^2–4x+x–4=0⇔x(x–4)+(x–4)=0`

    `⇔ (x – 4)(x + 1) = 0 ⇔ x – 4 = 0` hoặc `x + 1 = 0`

    `⇔ x = 4` hoặc `x = -1`

    Tập nghiệm của phương trình: `S = {4; -1}`

     

    0
    2021-09-15T22:46:42+00:00

    $\text{Đáp án + Giải thích các bước giải:}$

    `a//(x-1)(x^{2}+x+1)-2x=x(x-1)(x+1)`

    `<=>x^{3}-1-2x=x(x^{2}-1)`

    `<=>x^{3}-2x-1=x^{3}-x`

    `<=>x^{3}-x^{3}-2x+x=1`

    `<=>-x=1`

    `<=>x=-1`

    `\text{Vậy}` `S={-1}`

    `b//x^{2}-3x-4=0`

    `<=>(x^{2}-4x)+(x-4)=0`

    `<=>x(x-4)+(x-4)=0`

    `<=>(x-4)(x+1)=0`

    `<=>` \(\left[ \begin{array}{l}x-4=0\\x+1=0\end{array} \right.\) 

    `<=>` \(\left[ \begin{array}{l}x=4\\x=-1\end{array} \right.\) 

    `\text{Vậy}` `S={4;-1}`

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )